Regulamentação interna do relacionamento da Universidade Federal da Paraíba com fundações de apoio: um estudo sobre fluxos administrativos e sua aderência aos normativos vigentes - Arruda, Arthur Barbosa (2021)
This work sought to analyze how the Federal University of Paraíba (UFPB) is organized within its relationship with the Support Foundations of Higher Education Institutions, as regulated by Law No. 8.958/94 and internally regulated by CONSUNI Resolution No. 35/2013, describing the process of concluding, monitoring and inspecting the agreements, covenants and contracts signed with such entities. For this purpose, in light of the institutional rules (bylaw, regulations and internal resolutions), as well as the document analysis (administrative processes, legal opinions, history of procedural movement, audit reports, sectorial guidance manuals), besides to practical observance, as a public servant acting in the Coordination of Agreements (CODECON), Institutional Flowcharts were built, that represent the entire internal procedural flow, in which the sectors and their respective attributions were identified and divergences between what is formally regulated and the routine practices of the university were highlighted. It is a diagnosis resulting from a case study, with a qualitative approach and an exploratory-descriptive objective, based on documentary and bibliographic research. From the results obtained, the need to update internal regulations was indicated, as a measure of suitability, better definition of procedural flows and purge of the vulnerabilities of the relationship model implemented by UFPB with its supporting foundations. At the end, an orientation table is presented, with vectors describing the problems identified and vectors describing the actions expected to overcome them.